Perbedaan Pengaruh Paparan Musik Mozart, Beethoven dan Chopin Selama Kebuntingan Terhadap Ekspresi Brain Derived Neurotrophic Factor Di Crebellum Rattus norvegicus Baru Lahir - Pitria Permatasari (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 1970)
Indonesia's Human Development Index(HDI) for 2015 was ranked 113 out of 188 countries.Education would be needed to raise HDI’s rank. Oneprinciple component of education is the quality of thebrain. BDNF expression in the brain was affected bymany stimuli. Mozart classical music had aneurobiological effect which had ability to increaseBDNF. Whereas, other classical musics such asBeethoven and Chopin had never been studied. Thisstudy aims to cerebellum’s BDNF expression in theoffspring of Rattus norvegicus that ere exposed tothe Mozart , Beethoven, Chopin during pregnancy.The method used is pure laboratoryexperiment with posttest only control group design.The variables measured were BDNF expression inthe brain. The samples were divided into 4 groups ofeach 6 rats.The results showed that significantdifferences in BDNF expressions between controlgroup and Mozart (p=0,023; p<0,05), betweenMozart group and Chopin (p=0,003). There were nostatistically detected differences between controlgroup and Beethoven (p=0,256), control group andChopin (p=0,684), Mozart group and Beethoven(p=0,092) and Beethoven group and Chopin(p=0,292). Based on the above results it can beconcluded that the exposure of Mozart’s musicduring pregnancy had a higher expression of BDNFin the offspring-rat’s cerebellum compare to thosewhich exposed by Beethoven and Chopin’s music.